Primary Hepatic Lymphoma Presenting as an Acute Abdomen in a Young Female Patient: A Case Report and Literature Review - Walid E. Abdelrahim; Kamal E. Mohamed; Salwa O. Mekki; Eltaib A. Saad (Case Reports in Surgery)
We report a rare case of primary hepatic lymphoma (PHL) in a hepatitis B virus- (HBV-) infected young female patient who presented with right upper abdominal pain, nausea, and vomiting for a few days. The preoperative diagnosis was difficult due to the rarity of the disease and the presence of a solitary hypodense mass in the left lobe of the liver on contrast-enhanced computed tomography (CT) scan with a normal alpha-fetoprotein (AFP) and negative cytology. She underwent an uneventful extended left hemihepatectomy, and the surgical biopsy revealed a PHL—of diffuse large B-cell lymphoma (DLBCL) type—with negative resection margins. She received adjuvant combination chemotherapy and remained disease-free with normal serial radiology over a 2-year follow-up period.